VAT on medical supplies in South Africa: A critical analysis of whether the VATCOM's argument to standard rate medical supplies in 1991 still holds true - Hablutzel, Cuan (Department of Finance and Tax, 2022)
This paper aims to critically evaluate whether the existing VAT consequences on medical care services (and goods) is still relevant and valid given the developments within the South African economy since 1991, when VAT was first introduced in South Africa. Furthermore, this paper seeks to identify alternative VAT consequences that could be utilised if it is considered that the existing VAT consequences on medical care services and goods are no longer relevant and valid. Medical services and goods currently receive no concessional VAT treatment. This is because, when VAT was first implemented in 1991, patients of lower- and middle-income classes used the State medical systems and hence only paid nominal VAT or no VAT on their medical services. Therefore, VAT did not significantly impact them. Furthermore, services which had higher input costs would be negatively affected by exempting these services from VAT. However, the private healthcare system has increased significantly since the adoption of VAT in 1991. In today's economy, the private sector accounts for over 50% of healthcare spending in South Africa (Department of Health, 2017:42). The majority of this, however, is funded via medical aid, and only 14% of this expenditure is recorded as occurring from out-of-pocket plans (RH Bophelo , 2017). Therefore, the Value-Added Tax Committee's (“VATCOM's”) reasoning for not zero-rating VAT on medical care services and goods in 1991, was because it only impacted a nominal amount of the economy as a result of people using the State's healthcare system and, hence, only having to pay nominal VAT. It needs to be questioned if this is still relevant and valid in today's more robust South African economy. This is as a result of the ever-increasing portion of the economy who are either required to pay for private medical services, are not covered by medical aid, or need to add on an additional 15% (National Treasury, 2018:11) on top of the already expensive cost of these services due to the standard-rating of VAT for these supplies in South Africa. When South Africa first implemented its VAT Act it was based on the New Zealand model for General Sales Tax (Lang, et al., 2009: 264). Under the New Zealand GST model, healthcare services were standard-rated (New Zealand Government, 1985), hence providing reason as to why South Africa standard-rated medical services. However, Australia, who adopted GST in 2000, implemented healthcare as a GST free (zero-rated VAT) supply (Office of Parliamentary Counsel, 1999:98). Further to this, the United Arab Emirates, which is one of the most recent countries to introduce the VAT system into their economy, in 2018 (Deloitte, 2017:4), healthcare services from VAT (President of the United Arab Emirates, 2017:20). Additionally, the increased number of private healthcare institutions and the reliance on private medical care providers in South Africa (not to mention the fact that there is no concessional treatment, even though this healthcare system not only positively benefits patients receiving the healthcare and the South African Healthcare system, but also the South African economy as a whole) brings into question the validity and relevance of the current treatment of VAT on medical goods and services. When the current consequences of the legislation do not fully fulfil the intentions of the Vat Act, the legislation needs to be reconsidered and the tax consequences thereof re-evaluated. The preferred alternative VAT treatment recommended is for medical services and supplies, as well as medical insurance, to be zero-rated. This will allow for a reduced cost of providing these goods and service. Furthermore, zero-rating will alleviate the competitive disadvantage that private medical care suppliers are placed under as result of the substantial government presence in the public healthcare system. Additionally, it will decrease the burden of VAT being added to charges for medical services and goods, as well as decreasing the burden of VAT on medical insurance that is non-recoverable. An alternative VAT treatment (should the zero-rated approach fail) would be to exempt the supply of medical care services and goods, or to tax the supply thereof at a reduced rate. However, the high input cost being “trapped” if it were VAT exempt (in addition to the high administration complexity under a reduced VAT rate system) results in standard-rating of supplies being recommended ahead of these other concessional VAT treatments.